Protective vaccinations - contemporary dilemmas of holistic and traditional medicine - Salwa, Agata Anna (Journal of Education, Health and Sport, 2018)
Introduction and purpose of the work. Vaccinations, as one of the key achievements in medicine, is an important element of pursuing health policy at the national and global level. Systematic immunization of children and adults has improved quality and extended life expectancy. For each society, in addition to individual protection obtained by administering vaccinations, it is very important to achieve collective resistance. There have been reports of serious side effects of vaccination recently. On the Internet forums there is a fight between vaccine proponents and their skeptics. In Poland and in Europe, there is a growing reluctance of society and a downward trend in child immunization. The aim of the work is to identify contemporary parents’ dilemmas in the aspect of holistic and traditional medicine. Summary. Identifying the needs of modifications to the immunization program, including how to implement them along with justification, on the identification of connections between mass media, health service and other interested parties will help to develop a common ground for the perception of population implantation. It will be used to plan methods to improve education not only for parents but also for health care professionals: educational programs, training conferences or individually designed awareness-raising interventions based on reliable, comprehensive free access to knowledge.